2019
DOI: 10.2478/rsc-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Return migration and re-integration of returnees challenges in the origin country

Abstract: Return migration, traditionally not a well-studied and often neglected area, is becoming an important component of the international migration debate. Reintegration is an essential part of return migration and identified as a complex process that is experienced differently by returnees. The adaptation of immigrants in the host country has been extensively studied, while much less attention has been paid to economic and socio-cultural reintegration and the difficulties return migrants face once they come back t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The findings are in line with the previous literature that postulates that the prevalence of common mental disorders was found to be 27.6% among migrant returnees (Habtamu & Zeleke, 2017). Moreover, different studies found that return migrants of a young age are more likely to face psychological distress after their return (Hautaniemi et al, 2013;Ndreka, 2019;Yendaw et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The findings are in line with the previous literature that postulates that the prevalence of common mental disorders was found to be 27.6% among migrant returnees (Habtamu & Zeleke, 2017). Moreover, different studies found that return migrants of a young age are more likely to face psychological distress after their return (Hautaniemi et al, 2013;Ndreka, 2019;Yendaw et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…According to the Organization for Economic Co-operation and Development (OECD), 20-50% of migrants return to their place of origin or emigrate to a third country within five years of arriving in their initial destination [11]. Given the intensity and scope of return migration, it is not surprising that this topic is increasingly being discussed by academics in the 21st century [12].…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…The issue of voluntary return migration has remained invisible for a long time in the context of international migration and mobility studies (Arowolo, 2000;Weber, 2015Ndreka, 2019. According to the International Organization for Migration (IOM), about half of international migrants return annually to their countries of origin.…”
Section: Introductionmentioning
confidence: 99%